UPAYA HUKUM PEMERINTAH DESA DALAM MENANGANI MASALAH PENCURIAN DI DESA LABU KECAMATAN PUDING BESAR KABUPATEN BANGKA - Rahmiati Ranti Pawari (Justici, 2022)
Stealing is a problem that often happen be environmented society. With existence the mentioned stealing becoming society to feel not safe, with that government has an obligation to to overcome the mentioned problem. this Research to use it the quantitative research method descriptive, that is to descript it an incident that being happen and research data be done to use it kuesioner and also the interview that be done directly to to get it the accurate research result. research Result show that factor from existence action of stealing in Pumpkin village is from environment factor, and effort from Pumpkin village government at this time be told yet maximal, its lessly action from government mentioned expecting society so that village government to can to active it back ronda's post like that ever be done be yeared-year previous, so that can stealing to lesson action in village mentioned.